A vic-dioxime ligand bearing fluorescent coumarin moieties and its complexes; preparation, spectroscopy, and electrochemistry - ÖZKAYA, ALİ RIZA (TAYLOR & FRANCIS LTD, 2008)
The synthesis of a new vic-dioxime ligand, N,N'(2)-dihydroxy-O-1,O-2-bis(4-methyl-2-oxo-2H-chromen-7-yl)oxalimidamid (LH2) (1), bearing functional coumarins and its soluble mono- {Ni(II), Cu(II), Co(II)} and dinuclear {UO2(II)} complexes are presented. The fluorescence properties due to the 7-hydroxy-4-methylcoumarin fluorophore, which is conjugated with vic-dioxime that functions as the MN4 core of 1 and its complexes, are also reported. The formation of coordination complexes resulted in the blue shift in excitation spectrum and fluorescence quenching of 1. Both mononuclear {(LH)(2)M, M=Ni(II), Cu(II), and Co(II)} and homodinuclear {(LH)(2)(UO2)(2)(OH)(2))} complexes have been obtained with metal : ligand ratios of 1 : 2 and 2 : 2, respectively. The characterizations of the new compounds were made by elemental analysis, H-1-NMR, FT-IR, UV-Vis, and LCMS data. Redox behavior of 1, involving oxime and coumarin moieties, and its complexes with Ni(II), Cu(II), Co(II) and UO2(II) were investigated by cyclic voltammetry. The comparison of the electrochemical behavior of 1 with its complexes enabled us to identify metal-, oxime- and coumarin-based signals.
Keywords: vic-dioxime complexes; coumarin; fluorescence; nickel; copper; cobalt; uranyl; cyclic voltammetry; TRINUCLEAR COMPLEXES; DINUCLEAR COMPLEXES; REDOX PROPERTIES; METAL-COMPLEXES; NI COMPLEX; (E,E)M M; MONONUCLEAR; NICKEL(II); COPPER(II); IONS